Lucionema balatonense gen. et sp. n., a new nematode of a new family Lucionematidae fam. n. (Dracunculoidea) from the swimbladder of the European pikeperch, Stizostedion lucioperca (Pisces) - Moravec, F; Molnár, K; Székely, C (Folia parasitologica, 1998)
A new nematode genus and species, Lucionema balatonense gen. et sp. n., is described from the swimbladder of the European pikeperch, Stizostedion lucioperca (L.), from Lake Balaton in Hungary; a new dracunculoid family Lucionematidae fam. n. is established to accommodate it. The hitherto monotypic family Lucionematidae shows affinities with the families Skrjabillanidae and Daniconematidae, differing from them mainly in having simple oesophagus without external oesophageal glands and the vulva situated near the middle of body; from the first family also in the absence of the buccal capsule and the bursa-like caudal alae in the male. The genus Lucionema gen. n. is characterized mainly by the presence of 8 cephalic papillae in two circlets, absence of spicules, presence of the copulatory plate, only 2 pairs of postanal papillae in the male, and by the distal part of the monodelphic uterus forming a posteriorly directed coil. The body length of L. balatonense females is 1074-1782 microns, that of the only available male 770 microns. A key to the families of the Dracunculoidea is presented.
Keywords: okounovití; Animals; Hungary; Female; zvířata; vzdušné vaky; Maďarsko; mužské pohlaví; Dracunculoidea; Male; Perches; Air Sacs; ženské pohlaví